ISLAMIC EDUCATION IN THE NATIONAL EDUCATION SYSTEM - Hodiqotul Atfaliyah; Yosie Kristin Pandriyani; Wasehudin; Aceng Hasani; Abdul Muin (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
Islamic education holds a strategic position in Indonesia's national education system because it plays a role in holistically shaping the character, morals, and spirituality of students. This study aims to analyze the position, role, and implementation of Islamic education within the national education system, while also identifying challenges and opportunities for its development in the modern era. This study uses a qualitative approach with library research methods. Data were collected through a review of various scientific sources such as academic books, reputable journal articles, and relevant educational policy documents. Data analysis was conducted descriptively and analytically through the stages of data reduction, categorization, interpretation, and drawing conclusions. The results show that Islamic education has been normatively and structurally integrated into the national education system, as reflected in educational regulations and the existence of Islamic educational institutions such as madrasahs, Islamic boarding schools, and religious education in public schools. In practice, Islamic education contributes to the internalization of religious values, the formation of noble morals, and the strengthening of students' moral and cultural identities. The discussion shows that the integration of Islamic education into the national education system has made a significant contribution to creating a generation that is not only intellectually superior but also possesses moral and spiritual integrity. However, strengthening curriculum quality, enhancing educator competency, and fostering technology-based learning innovations are challenges that require a systematic response. Therefore, synergy between education policy, curriculum development, and adaptive pedagogical practices is necessary to ensure Islamic education can respond to the dynamics of societal development and global demands.